TANGGUNG JAWAB NOTARIS DALAM PEMBUATAN AKTA PENGGUNAAN SAHAM NOMINEE DALAM PENANAMAN MODAL ASING - YANTI MAYA SARI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Budimnan Ginting, SH, MHum2.  Dr. T. Keizerina Devi A, SH, CN, MHum3.  Dr. Mahmul Siregar, SH, MHum A Notary is a public official who has the authority to draw up authentic deeds and has other authorities as stipulated in Article 1 of Law No. 30/2004 on Notarial Position as it is amended to Law No. 2/2014 on the amendment of Law No. 30/2004 on Notarial Position. The research used juridical normative and descriptive analytic method. The result of the research shows that legal certainty which firmly prohibits a nominee contract is stipulated in Article 33, paragraphs 1 and 2 of Law No. 25/2007 on Capital Investment. It is recommended that a Notary firmly refuse to make a nominee contract, especially when foreign investors want to control the majority of shares in an Indonesian company.Keywords: Notary, Nominee Contract, Capital Investment, Beneficiary Owner, Legal Owner